Biscuit goes to school - Capucilli, Alyssa Satin, 1957-; Schories, Pat ([New York] : HarperCollins, 2002)
A dog follows the bus to school, where he meets the teacher and takes part in the activities of the class.
100
Accelerated Reader AR
Keywords: Dogs -- Fiction; Schools -- Fiction